C and CP violation in effective field theories - Hakan Akdag; Bastian Kubis; Andreas Wirzba (Journal of High Energy Physics, 2023)
Abstract The quest for new sources of the simultaneous violation of C and CP symmetry was popular in the 1960s and has since been mostly neglected for more than half a century. In this work we revisit fundamental quark-level operators that break C and CP up to and including mass dimension 8 for flavor-conserving transitions, relying on the complete operator sets of the so-called Standard Model effective field theory and the low-energy effective field theory. With the formalism of chiral perturbation theory, we match these quark operators to light-meson physics, derive C- and CP -odd Lagrangians for several processes in the η, η ' , and pion sectors, and furthermore, as a proof of principle, give estimates for the respective observables in explicit dependence of the underlying high-energy scale for new physics.